Animal lullabies - Prap, Lila 1955- (NorthSouth Books, 2006)
Rhyming text shows what kinds of lullabies animal parents, such as an elephant, a fish, or a snake, might sing to their young
Keywords: Tiere; Kinderreim; Einschlafen; Lullabies / Pictorial works / Juvenile fiction; Animals / Pictorial works / Juvenile fiction; Stories in rhyme; Lullabies / Fiction; Animals / Fiction; Tiere / Wiegenlied / Bilderbuch; Wiegenlied / Tiere / Bilderbuch; Animals; Lullabies; Children's stories / Pictorial works; Bilderbuch; Kinderbuch; Anthologie